Artificial Intelligence in Islamic Education Management and Institutional Performance: The Mediating Role of Strategic Leadership at Islamic Religious Higher Education Institutions - Sartika Mahmud; Ibnu Rawandhy N. Hula; Suleman D. Kadir (Lembaga Bale Literasi, 2026)
Digital transformation in higher education has positioned Artificial Intelligence (AI) as a strategic element of institutional governance rather than merely a technical tool. This study aims to analyze patterns of AI implementation, to explain the qualitative mediating role of strategic leadership in institutional performance, and to identify the integration of Islamic values into technology governance at IAIN Sultan Amai Gorontalo. The study employs a qualitative approach with a single-case study design. Data were collected through semi-structured interviews, passive observation, and document analysis involving institutional leaders, technical unit managers, lecturers, and administrative staff. The data were analyzed through data condensation, coding, theme development, matrix presentation, and interpretive verification. The findings indicate that AI implementation remains at an emerging stage and is selectively applied through academic dashboards, basic predictive analytics, and administrative automation. Strategic leadership functions as an interpretive and coordinative mechanism that connects technological outputs with decision-making, resource allocation, resistance management, and the strengthening of digital literacy. AI implementation supports service efficiency, systematization of quality reporting, and audit readiness, yet its benefits depend upon sustained training, infrastructure stability, policy consistency, and leadership commitment. The values of maqashid al-sharia, data stewardship, public benefit (maslahah), and human-in-the-loop principles constitute the normative foundation of AI implementation. Because the study relies on a single case, these findings are contextual and require further examination through multi-site studies at other State Islamic Higher Education Institutions with different institutional characteristics.